Naming Academic Libraries: Is Institutional Identity Obscuring the Generous Benefactors and Illustrious Educators of Old? - Alice Crosetto; Thomas A Atwood (Names, 2012)
Abstract Identifying the individuals after whom academic libraries are named reveals interesting patterns. An examination of the libraries at traditionally grouped schools such as Ivy League, Seven Sisters, and Big Ten as well as the authors’ home state academic libraries illustrates the varying degrees of how libraries preserve their own history. Additionally, the research reveals that only fifty percent of these libraries are named primarily after alumni, presidents, educators and benefactors. Once named, libraries often experience name changes both officially or by popular usage. The authors propose that some library names change to reflect the current campus culture, while others hold steadfast to their historical naming practices. As libraries struggle to maintain their traditional image and at the same time pursue an identity as a transformative educational force, library names will continue to reflect the institution and community which they serve.